A water droplet motion energy harvester with wafer-level fabrication method. (30th April 2020) - Liu, Chaoran; Wang, Yishao; Sun, Peng; Chi, Jingu; Che, Lufeng; Zhou, Xiaofeng; Wang, Zuankai; Yang, Weihuang; Dong, Linxi; Wang, Gaofeng; Yang, Xun
Abstract: Water droplets are ubiquitous in nature and harvesting droplet kinetic energy has attracted a great deal of attention to meet the increasing worldwide energy demands. In this work, we report a water droplet motion energy harvester with the wafer-level fabrication method, which is based on the water–solid surface contact electrical double layer effect. A theoretical model is established to illuminate the water droplet motion energy harvesting mechanism. Guided by the model, an energy harvester is developed based on Micro Electro-Mechanical Systems compatible process technology, which achieve a wafer-level fabrication. The output performance of the energy harvester has been optimized by decreasing the electrode width and its interval. Experimental results also show that the output voltage can be improved by increasing the droplet volume and decreasing the ionic concentration. The optimized energy harvester exhibits an open circuit output peak voltage of 57.5 mV. This research provides an in-depth theoretical study and a practical guidance on water droplet kinetic energy harvesting.